2018
DOI: 10.1177/0013916518799149
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Trouble: Exploring Environmental Risk Information Avoidance Intentions.

Abstract: This study explores predictors of risk information avoidance intentions in the context of a novel environmental threat—induced earthquakes in Texas. Given the paucity of research on risk information avoidance, this work was guided by a cognitive information behavior model. Survey data ( N = 541) from a random sample of Texas adults allowed us to explore these variables. While previous research has shown risk information seeking intentions to be robustly guided by a number of constructs, our current data sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 99 publications
4
42
0
Order By: Relevance
“…The motivation for danger control enhances the information-seeking process, while the motivation for fear control spurs information avoidance ( Witte, 1994 ). More recently, Kahlor et al. (2020) fashioned an information avoidance model based on their earlier planned risk information-seeking model (PRISM) ( Kahlor, 2010 ), and the two models share similar predictors, although the dependent variables differ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The motivation for danger control enhances the information-seeking process, while the motivation for fear control spurs information avoidance ( Witte, 1994 ). More recently, Kahlor et al. (2020) fashioned an information avoidance model based on their earlier planned risk information-seeking model (PRISM) ( Kahlor, 2010 ), and the two models share similar predictors, although the dependent variables differ.…”
Section: Discussionmentioning
confidence: 99%
“…In some prior studies, the three terms— negative affect, anxiety , and cognitive dissonance —were often interchangeably used, and these studies often produced inconsistent results. For example, Kahlor et al. (2020) measured what they called the affective risk response in terms of the two dimensions of worry and fear ( Kahlor, 2010 ) and found a negative relationship between affective response and information avoidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While perhaps comforting in the moment, information avoidance, similar to threat denial and avoiding making a decision, can impede precautionary measures, even measures that may be within a person's means. Other research has shown that people avoid risk information about an environmental threat if they perceive that avoidance is normative (Kahlor, Olson, Markman, & Wang, ), and that lack of awareness of an environmental threat can lead to lack of preparation (Lindell & Perry, ). Yet, we know of no study that has examined how the burden of preparation might influence people's decisions to avoid threat‐related information.…”
Section: Introductionmentioning
confidence: 99%
“…While perhaps comforting in the moment, information avoidance, similar to threat denial and avoiding making a decision, can impede precautionary measures, even measures that may be within a person's means. Other research has shown that people avoid risk information about an environmental threat if they perceive that avoidance is normative (Kahlor, Olson, Markman, & Wang, 2018), and that lack of awareness of an environmental threat can lead to lack of preparation (Lindell & Perry, 2012).…”
Section: Introductionmentioning
confidence: 99%